Sosialisasi Teknologi Biogas di Desa Gentungan, Mojogedang sebagai Pendukung Integrated Farming System - Ina Nurtanti; Ardian Ozzy Wianto; Desna Ayu Wijayanti; Nisa Dwi Septiyanti (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Gentungan Village has established itself as one of the centers for organic farming in Mojogedang District. The village's rice field area spans 109.89 hectares, with a community of 150 farmer-breeders and a beef cattle population of 575 head. The community in Gentungan faces several key challenges, primarily concerning the management of cattle manure waste and dependence on fossil fuels such as LPG. To address these issues, an approach was taken to process cattle livestock waste into biogas. Biogas serves as an alternative energy source capable of replacing LPG for various household needs, including cooking. Biogas systems can be installed in individual households or collectively at the village level. The objective of this community service initiative is to conduct outreach on the utilization of beef cattle farming waste, which is currently not optimized—limited mostly to organic fertilizer production, with few utilizing it for biogas generation as a substitute for LPG energy. The partner for this program is the *Mulyo 1 Farmers Group*, consisting of farmer-breeders in Gentungan Village, Mojogedang District, Karanganyar Regency. The methods employed include conducting outreach sessions and providing direct assistance to farmers and breeders in the installation of biogas systems. The outcome of this service is the establishment of a 6-cubic meter fixed-dome type biogas installation, which can be utilized by the members of the Mulyo 1 Farmers Group as a substitute for LPG energy. As a result, this initiative helps reduce cattle waste while providing farmer-breeders with an alternative energy source to replace LPG.